Reactive Ethnic Formations and Panethnic Identities: The Creation of Latinos in the United States - Ramón A. Gutiérrez (Revue LISA)
This article delves into the complexity of ethnic identities in different national spaces and explores the emergence of panethnicity in the United States, which has become a phenomenon of significant sociological importance since the early 1970s. Specifically, it explores how individuals from Mexico, Puerto Rico, Cuba, Central America and South America came to think of themselves as tied politically as Latinos. This essay argues that such panethnicity can come from above, from state action to gather distinct national and ethnic identities, or it can come from below, from communities that band together for a common purpose.